HARMFUL EFFECTS OF MOBILE PHONES ON CHILDREN - Khamidov Bakhodir; Tojiev Khudoberdi; Juraev Rustamjon (Scholar Express Journals, 2024)
This article tells about one of the most common and global problem- the impact of mobile phones on children’s health and harmful effects on children’s development, especially the radiations from these devices are harmful for their developing brains, the article also discusses the advantages and disadvantages of mobile phones in our life.
Keywords: Smartphone Addiction; Physical And Mental Health; Excessive